Optimization of atrazine removal from synthetic groundwater by electrooxidation process using titanium dioxide and graphite electrodes - Turan, Nouha Bakaraki; Erkan, Hanife Sari; Caglak, Abdulkadir; Bakirdere, Sezgin; Engin, Guleda Onkal (TAYLOR & FRANCIS INC, 2020)
Atrazine is used in agriculture and is known for its high toxicity. It therefore poses a risk to surface and ground waters, and human life. In this study, an electrochemical method was optimized for atrazine removal from SGW using TiO2 and graphite electrodes. A comparison between one factor at a time period optimization and Box-Behnken design (BBD) optimization using RSM was carried out to select the optimum conditions. The results show excellent atrazine removal efficiency (99.70%) and close optimum conditions for both applied methods (pH 7 and 7.4; current 2.5 and 2 A and time 14 and 12.12 min, respectively).
Keywords: Atrazine; groundwater; electrochemical treatment; TiO2 electrode; graphite electrode; RESPONSE-SURFACE METHODOLOGY; WASTE-WATER TREATMENT; ELECTROCHEMICAL OXIDATION; HERBICIDE ATRAZINE; EFFICIENT REMOVAL; AQUEOUS-SOLUTION; HUMIC-ACID; PESTICIDE; DYE; DESIGN; Chemistry; Engineering